REVISION OF ELECTORAL ROLL AMID CACOPHONY AND CHEERS: A STUDY - Baranwal, Sanjay (International Journal of Research -GRANTHAALAYAH, 2025)
Success of democracy presupposes fair electoral process which includes preparation of a genuine electoral roll of the voters, a task performed by the ECI in India. To raise concern against ills in the exercise of this task is a democratic duty of a stakeholder but the concern must be corroborated by substantial evidences. ECI is exhibiting its duties in adherence to article 324 and 326 and Statutory Act of 1950 and 1960 to prepare electoral list. A democratic and transparent functioning of the ECI in preparing the electoral rolls should be acclaimed. ECI embarks upon innovations and initiatives to avert grievances of stakeholders which certainly paves way for a sanguine democracy in India.